A abordagem dos multiletramentos na criação de objetos digitais de ensino-aprendizagem com o PowerPoint - Schach, Letícia (2019)
The creation of digital teaching and learning objects (DTLO) that contemplate the multiliteracies, especially the multimodality, through the PowerPoint software in a multimodal and hypertextual perspective, is the subject matter of this research, which is grounded on the Applied Linguistics parameters, inside a qualitative-interpretive approach, in the form of an action research. Therefore the answer to the following question was sought: do the DTLO produced by teachers in a context of continuing education oriented to the use of technologies result in a product that contemplates the multiliteracies and the multimodality? Looking for answers to this question, the main objective was to verify if the DTLO created by teachers in a context of continuing education oriented to the use of technologies, specifically through PowerPoint, contemplate the multiliteracies. Specific objectives were also delimited: identifying how the participant teachers of the continuing education understand and allegedly use the Digital Information and Communication Technologies (DICT); identifying, after the course, if there was a new positioning of the teaching formation participants regarding the DICT; verifying if the approach made with technologies enabled the teachers to elaborate DTLO contemplating multiliteracies, especially the multimodality. Theoretically support this research the authors ALMEIDA (2000), KENSKI (1998, 2008, 2012), LEMKE (2010), LÉVY (2004), MORAN (2008), PONTE (2000), ROJO (2009, 2013, 2016, 2017), ROJO and MOURA (2012), SOARES (2000, 2002, 2004), VALENTE and ALMEIDA (1997), VAN LEEUWEN (2011), WILEY (2000), XAVIER (2004, 2006, 2009). The data were generated from questionnaires, from the researcher's fields notes and from the DTLO created during the teaching formation. It is possible to identify, at the end of the study, that the produced DTLO effectively approach the multiliteracies, especially the multimodality. The research also reveals the positive impacts of the teaching formation in the DICT area, being fundamental to capacitate the teacher so as to insert himself/herself and also move with competence and confidence in the contemporary digital world, rethinking and reformulating his/her pedagogical practice